Axial Dispersion and Back-mixing of Gas Phase in Pebble Bed Reactor - Rahman Al-Musafir (Tikrit Journal of Engineering Sciences, 2013)
Despite the worldwide attended of pebble bed reactors (PBRs), there is a lack of fundamental understanding of the complex flow pattern. In this work, the non-ideal flow behavior of the gas phase which is used for cooling has been investigated experimentally in a 0.3 m diameter pebble bed. The extent of mixing and dispersion of the gas phase has been qualified. The effect of gas velocity on the axial dispersion has been investigated with range from 0.05 to 0.6 m/s covering both the laminar and turbulent flow regimes. Glass bead particles of 1.2 cm diameter and 2.5 gm/cm3 which is randomly and closely packed have been used to mimic the pebbles. An advanced gas tracer technique was applied to measure the residence time distribution (RTD) of gas phase using impulse tracer. The axial dispersion coefficients of gas phase in the studied pebble bed have been estimated using the axial dispersion model (ADM). It was found that the flow pattern of the gas phase deviates from plug flow depending on the superficial gas velocity. The results showed that the dispersion of the gas reduces as the gas velocity and Reynolds numbers increased.